[(Z)-O-Ethyl N-(4-nitrophenyl)thiocarbamato-κS](triethylphosphine-κP)gold(I) - Soo Yei Ho; Edward R. T. Tiekink (Acta Crystallographica Section E, 2009)
In the title compound, [Au(C9H9N2O3S)(C6H15P)], two virtually identical molecules comprise the asymmetric unit. These are connected by Au...Au [3.6796 (4) Å] and Au...S [3.6325 (18) and 3.5471 (18) Å] contacts, forming a dimeric aggregate. The presence of intramolecular Au...O contacts [2.993 (5) and 2.957 (5) Å] is responsible for the slight deviations from the ideal linear coordination environments about the AuI ions. The conformation about the central C=N double bond is Z. Supramolecular chains sustained by π–π [3.573 (4) Å] and C—H...π interactions are evident in the crystal structure. These are connected into layers via weak intermolecular C—H...O interactions involving the nitro-group O atoms.